A quad band planar slotted microstrip patch antenna for wireless applications - Reshma Roy; Apurva Singh; Om Prakash Kumar; Tanweer Ali; Manohara Pai M. M. (Institute of Advanced Engineering and Science, 2020)
This research paper presents two different types of multiband patch antenna. The first design is a dual-band antenna and the second design is a quad-band antenna. Both the antennas have a compact size of , and is designed on FR4 substrate with loss tangent (=0.02, height (h)=1.6 mm, with dielectric constant of 4.4. The dual-band antenna operates at frequencies 3.9 and 5.71 GHz. These dual band operations are accomplished by utilizing L-shaped slot in the ground part and T-shaped slot in the radiating part of the patch antenna. The gain corresponding to the two frequency bands are 1.27 and 1.35 dB, respectively. The quad band antenna operates at frequencies 3.6, 4.9, 7.4 and 8 GHz. The gain corresponding to these frequencies are 0.18, 1.69, 2.25 and 3.99 dB. For achieving quad band operation from the dual band antenna the back plane L-shaped slot is modified by cutting a rectangular strip in the middle, hence dividing it into two different slots. The front plane is also modified by introducing two rectangular strips to the T-shaped patch. The proposed antenna shows multiband and has the advantage of simple structure compact size and good impedance matching. All the simulations of the proposed design are carried out in HFSS v.13.0.